Attributes of Perforator Flaps for Prophylatic Soft Tissue Augmentation Prior to Definitive Total Knee Arthroplasty - Azoury, Saïd C.; Stranix, John T.; Piper, Merisa; Kovach, Stephen J.; Hallock, Geoffrey G. (Journal of Reconstructive Microsurgery, 2019)
Background As our population ages, the demand for total knee arthroplasty (TKA) will dramatically increase to ensure an independent lifestyle with unimpeded and pain-free ambulation. Complications will be inevitable, especially in that patient with preexisting soft tissue deficits or extensive scarring in the knee region. Under these circumstances, prophylactic soft tissue augmentation should be strongly considered and be extremely beneficial.Methods A retrospective review of all TKA procedures at our institutions over the past two decades revealed seven patients who specifically had soft tissue augmentation prior to their definitive TKA. Each had a single perforator flap used to achieve this. In no cases was a muscle flap used for this purpose. Excluded were all patients who had a flap of any kind for coverage of an exposed prosthesis or to accomplish wound healing after the TKA.Results Seven perforator flaps were utilized in seven patients for soft tissue replacement prior to the ultimate TKA. For smaller defects in three patients, a local island medial sural artery perforator flap was used. For larger defects in four patients, an anterolateral thigh perforator free flap was necessary. All flaps were successful. The only complication was an implant infection after one anterolateral thigh free flap that required a revision arthroplasty that eventually allowed salvage. Unrestricted ambulation was possible in all patients except for one who had a preexisting contralateral below-knee amputation.Conclusion As the number of TKA procedures in the near future increases, prevention of the absolute number of complications becomes even more important. An awareness that any knee region suboptimal soft tissue base can lead to wound breakdown and then periprosthetic infection should alert all involved that prevention of this sequela can be best achieved by prior soft tissue augmentation. Preferably, this may be possible by capturing the assets of local and free perforator flaps.
Keywords: total knee arthroplasty; anterolateral thigh flap; anterolateral thigh; medial sural artery; perforator flap; medial sural artery perforator; knee prosthesis